2021
DOI: 10.1177/15910199211051830
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal angioplasty and stenting in acute stroke caused by basilar artery steno-occlusive disease: The experience of a single stroke centre

Abstract: Background Percutaneous transluminal angioplasty and stenting in acute stroke due to severe basilar artery stenosis or basilar artery occlusion remain a matter of debate. The higher risk of stroke recurrence in patients with vertebrobasilar stenosis compared to anterior circulation atherosclerotic disease creates high expectations concerning endovascular approaches. This study aims to review our experience with percutaneous transluminal angioplasty and stenting in acute stroke caused by basilar artery steno-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This relatively low hemorrhage rate can be attributed to the fact that recanalization of the occluded vessel was achieved through direct aspiration in nearly half of the cases. Machado et al ( 24 ) reported a favorable prognosis rate of 43.5% at 90 days post-endovascular treatment of acute BAO. Similarly, in an international multicenter registry study that included 148 patients with BAO who underwent endovascular treatment, 79% achieved revascularization, and 34% achieved a favorable prognosis ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This relatively low hemorrhage rate can be attributed to the fact that recanalization of the occluded vessel was achieved through direct aspiration in nearly half of the cases. Machado et al ( 24 ) reported a favorable prognosis rate of 43.5% at 90 days post-endovascular treatment of acute BAO. Similarly, in an international multicenter registry study that included 148 patients with BAO who underwent endovascular treatment, 79% achieved revascularization, and 34% achieved a favorable prognosis ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Warfarin-Aspirin Symptomatic Intracranial Disease (WASID) group compared the safety and efficacy of the two antithrombotic agents in a multicentric post hoc analysis of 68 patients with a stroke secondary to a 50-99% BAS [15]. They found that 23% of patients taking aspirin had a subsequent stroke in the same vascular territory as the stenotic artery compared with 10% for warfarin.…”
Section: Management Of Basilar Artery Stroke: Current Pitfalls and Pe...mentioning
confidence: 99%
“…There is currently no strong evidence to support emergent stenting after successful thrombectomy, as the data are scarce and limited to case series and cohort studies (26,27,(52)(53)(54)(55)(56). Li et al performed a comparative analysis of 184 consecutive patients with severe stenosis after thrombectomy, in which 64 patients underwent rescue angioplasty or stenting, and 120 patients were managed medically.…”
Section: Emergent Stenting Of Icas Following Successful Thrombectomymentioning
confidence: 99%